Kekuatan Kalimat dalam Membangun Narasi Konflik : Analisis Sintaksis Terhadap Berita WNA Ngamuk di Kalibata City - Tasya Aflina Silaban; Tiarma Rokasih Sagala; Esmeralda Sitohang; Anggun Syahputri; Anggia Puteri; Frina Barus (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the power of sentence structures in constructing conflict narratives in news reports about a foreign national (WNA) causing a disturbance in Kalibata City. Through a syntactic analysis approach, this research examines how sentence structures, lexical choices, and information hierarchies influence public perception of the incident. The data is analyzed using modern syntactic theory and critical discourse analysis, referencing the works of Fairclough (2020) and Halliday (2021), which emphasize the relationship between language structures and media power. The findings reveal that the use of passive constructions, subordinate clauses, and repetition of conflict-related elements intensify the dramatization and tension within the narrative. Thus, syntactic power in news texts does not merely convey information but also constructs a social perception of the reported conflict. These findings contribute to critical linguistic studies and media literacy.